2013
DOI: 10.1186/2193-7680-2-8
|View full text |Cite
|
Sign up to set email alerts
|

Defining the types of counterfeiters, counterfeiting, and offender organizations

Abstract: Background: Product counterfeiting is growing in scope, scale, and threat. This includes awareness of deceptive and non-deceptive counterfeiting types. (This paper does not consider copyright or digital piracy, currency counterfeiting, fraudulent documents, or artwork forgery.) In response, many organizations are focusing on product counterfeiting including INTERPOL, International Standards Organization, World Health Organization, World Customs Organization, and the U.S. Department of Justice. The goal of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 23 publications
0
42
1
2
Order By: Relevance
“…Our previous research, which identified the types of criminals that were associated with product-counterfeiting incidents ranging from recreational to professional, are defined in Table 1 (Spink and Moyer 2011b;Spink et al 2013). …”
Section: Types Of Counterfeitersmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous research, which identified the types of criminals that were associated with product-counterfeiting incidents ranging from recreational to professional, are defined in Table 1 (Spink and Moyer 2011b;Spink et al 2013). …”
Section: Types Of Counterfeitersmentioning
confidence: 99%
“…It is important to note that the concepts are often more generally referred to as fraud since in many situations the incidents are not a violation of intellectual property rights laws or not technically the violation of a criminal statute (Spink et al 2013). Considering fraud as the threat is a holistic and all-encompassing concept.…”
Section: Types Of Counterfeitingmentioning
confidence: 99%
See 2 more Smart Citations
“…This literature tends to deal with technical and evidential issues and seldom strays into criminological debate. The bulk of academic publications on economically motivated adulteration (EMA) are based upon the US work of Spink and colleagues (Spink 2011;Spink and Moyer 2011a and b;Spink 2012;Moore Spink and Lipp 2012;Spink, Moyer, Park, and Heinonen, 2013;Spink, Moyer, Park and Heinonen, 2014) and generally covers structural issues which lead to the practice of fraud. In particular, the issue of fraudulent mislabeling of one type of food as another is a hot topic (for example, the process of labeling horsemeat as prime beef or adulterating beef with cheaper horsemeat or horse protein to inflate the profit).…”
Section: Considering the Scientific Literaturementioning
confidence: 99%